Project planning and control using spreadsheet for a sub-contractor company [electronic resource] - 450149 Loqman Elias; Fakulti Kejuruteraan Mekanikal (Skudai : Universiti Teknologi Malaysia, 2007)
Project Paper (Sarjana Muda Kejuruteraan Mekanikal (Industri)) - Universiti Teknologi Malaysia, 2007